Analisis Tingkat Kebugaran Jasmani Pemain Bulu Tangkis Usia 10-12 Tahun Di PB Ganesha Kota Batu - Putra, Enrico Rendra Pratama Putra; Amiq, Fahrial (Populer: Jurnal Penelitian Mahasiswa, 2025)
One of the needs of every person is physical fitness. A good physical fitness condition is able to strengthen the physique that can support effectively and efficiently and reduce excessive fatigue. The purpose of this study is to examine the level of physical fitness of badminton players PB Ganesha Batu City. Data was collected through a survey design with descriptive quantitative. The subjects used were PB Ganesha badminton players Batu City. The instruments applied were the Indonesian Physical Fitness Test (TKJI) 10-12 years and observation as a non-test instrument. Data analysis applied descriptive statistics. The results of the analysis of the physical fitness level of badminton players aged 10-12 years PB Ganesha Kota Batu, namely a total of 20 badminton players, there are 9 players in the good category with a percentage of 45% and 11 badminton players in the medium category with a percentage of 55%. In conclusion, the level of physical fitness of badminton players PB Ganesha Batu City at the age of 10-12 years is categorized as moderate, so the advice given is that badminton players are more motivated to improve physical fitness.